2015
DOI: 10.4103/0253-7613.165192
|View full text |Cite
|
Sign up to set email alerts
|

Short-term differences in drug prices after implementation of the national essential medicines system: A case study in rural Jiangxi Province, China

Abstract: Objectives:China's 2009 national essential medicine system (NEMS) was designed to reduce prices through a zero-markup policy and a centralized bidding system. To analyze NEMS's short-term impact on drug prices, we estimated the retail and wholesale prices before and after the reform at health institutions in rural Jiangxi Province.Materials and Methods:We undertook two cross-sectional surveys of prices of 39 medicines in November 2008 and May 2010, calculated inflation adjusted prices, and used the Wilcoxon si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…The instantaneous changes in diabetes and CHD are statistically significant, and the analysis decreased by 45.51 yuan and 77.46 yuan, while there is no significant difference in CHD. This illustrates that, on the whole, the ZMDP effectively regulates the drug cost for different diseases, has universal applicability, consistent with the study's findings by Wang [30]. Chao's [31] research also shows that reasonable prices for essential drugs and the implementation of the ZMDP can reduce the average cost of prescriptions.…”
Section: Discussionsupporting
confidence: 84%
“…The instantaneous changes in diabetes and CHD are statistically significant, and the analysis decreased by 45.51 yuan and 77.46 yuan, while there is no significant difference in CHD. This illustrates that, on the whole, the ZMDP effectively regulates the drug cost for different diseases, has universal applicability, consistent with the study's findings by Wang [30]. Chao's [31] research also shows that reasonable prices for essential drugs and the implementation of the ZMDP can reduce the average cost of prescriptions.…”
Section: Discussionsupporting
confidence: 84%
“…This result revealed that the CPMP failed to either reduce the drug expense or combat its growth. This discovery was also in line with currently available studies [ 22 , 23 , 26 ], where the CPMP was reported to be insufficient not only to lower drug wholesale prices but also to bring down drug expenses. The failure of CPMP may be justified by the fact that health institutions had limited incentives to lower their purchase prices (wholesale prices) to save money because of the ZMDP [ 26 ].…”
Section: Discussionsupporting
confidence: 84%
“…This discovery was also in line with currently available studies [ 22 , 23 , 26 ], where the CPMP was reported to be insufficient not only to lower drug wholesale prices but also to bring down drug expenses. The failure of CPMP may be justified by the fact that health institutions had limited incentives to lower their purchase prices (wholesale prices) to save money because of the ZMDP [ 26 ]. Moreover, centralized drug procurement system has been in place for more than a decade and the CPMP launched in Sanming city was nothing more than a new version of it and therefore, it is reasonable to believe that pharmaceutical companies has already adapted to the CPMP well.…”
Section: Discussionsupporting
confidence: 84%
“…[ 2 6 ] Not surprisingly, the data from Jiangxi and Shaanxi provinces and nation-level data of all provinces also show that the NEMS, particularly the ZMDP for essential medicines, led to significant reduction in per-visit medicine charges in rural areas. [ 3 , 4 , 7 ] Additional effects are physician prescription-pattern changes and differences in medicine prices between urban and rural healthcare institutions. [ 1 , 2 , 8 ] However, the increase or decrease of the medicine or healthcare charges was largely dependently on the hospital levels as Wang et al showed.…”
Section: Introductionmentioning
confidence: 99%